Voskarides, Sotos - (:unkn) unknown (My University, 2026)
He possesses a PhD in Telemedicine (Brunel University, London), a BSc (Hons) Degree in Electrical and Electronic Engineering (University of Westminster, London) and a Diploma of Technician Engineer in Electrical Engineering (Higher Technical Institute, Cyprus). He worked in Cyprus for many years as a lecturer of Electronics and Telecommunications (Frederick Polytechnic, 1979-86, Intercollege, 1987 and Higher Technical Institute since 2007). During the period 1987-97 he was the Director of Voskarides Institute of Telecommunications. His research interests are mainly telemedicine, tele-robotics, wired and wireless networks, satellite communications and distributed sensors. He developed the Tele-Ortho-Paidics System (TOP) and he is one of the two coordinators of the French-Cyprus Research Project MARTE (Tele-ultrasound examination using robotics).